(untitled) (Journal of Atomic and Molecular Sciences, 2014)
By numerically solving the Maxwell-Bloch equations using an iterative predictor-corrector finite-difference time-domain (FDTD) technique, the optical limiting (OL) and two-photon absorption (TPA) properties for femtosecond laser pulses in a strong TPA organic molecular (4,4'-bis (di-n-butylamino) stilbene (BDBAS))medium are studied. The medium has obvious OL behavior in a certain intensity region which is dependent on the propagation distance, sample concentration, input pulse width and effect of optical ionization. Moreover, dynamical TPA cross sections are obtained, showing an increasing trend with the broadening of the pulse width and the propagation distance in the femtosecond time domain.